Dear David,
I read with considerable interest your "Program Proving and Applicative Languages", but when I tried to apply your techniques to the first slightly more ambitious example my assistant W.H.J. Feijen came up with, it turned out to be a very humbling experience: I clearly lacked the knack of dealing with SASL programs.
Consider the following short SASL definitions (my syntax! I trust you will forgive me that)
def k x y (p : q) =
if p ≤ y → k (x + 1) y q
⌷ p > y → x : k x (y + 1) (p : q)
fi ;
def g = k 0 0 f
Here f is supposed to be ascending, i.e. to satisfy (P_{0} f ) with
P_{0} (a : b : c) = a ≤ b ∧ P_{0} (b : c)
and unbounded, i.e. to satisfy (Ay : y ≥ 0: P_{1} y f ) withP_{1} y (p : q) = p > y ∨ (P_{1} y q).
When f is ascending and unbounded, it is clearly an infinite list. (I try to use the more positive term "continued concatenation" for that, but that is another story.)
You would do me a great service by showing me a proof that when f is ascending and unbounded, g is ascending and unbounded.
The precise formal relation between g and f is that for all y ≥ 0
sub y g = (N x : x ≥ 0 : y ≥ (sub x f )) 
(0)

def sub n (p : q) =and the (N ... ) should be read as: the number of distinct values x in the range x ≥ 0 such that y ≥ (sub x f). You would do me a great service by showing me as well, how you would prove (0). I am looking forward to your reply.
if n = 0 → p
⌷ n > 0 → sub (n−1) q
fi
With my greetings and best wishes,
Yours ever
Edsger
5 November 1980